Development of Magnetic Field Energy Generator - MUSZAFFARSHAM, AZFARRIDZWAN; Osman, Shahrul Azmir (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The primary issue with the conventional generator is it requires diesel or petrol to produce electricity. A standard 5-kilowatt generator will typically consume about 3 liters per hour. The price of fuel does fluctuate, which can make running this type of portable generators expensive over a prolonged period of time. Plus, it can be such a waste just to light up a stall. Thus, a view to overcoming both and noise pollution at the night market, a perpetual magnetic energy generator which is smaller in size, portable, light-weighted as well as easy to handle is proposed later in this research paper.  In short, the research is focused on designing and developing an affordable Neodymium-based free energy generator that operates continuously without depending on any external source. The repulsive force between the Neodymium magnets produces a torque that serves as a prime mover for the rotor arm. So, the magnetic generator converts the mechanical energy gotten from the motion of magnets moving under repulsive force, into electrical energy using a DC motor. The DC motor will generate voltage to light up the lamp.